Effect of dexmedetomidine in children undergoing general anesthesia with sevoflurane: a meta-analysis - Marco Aurélio Soares Amorim (Brazilian Journal of Anesthesiology, 2017)
Background and objectives: Sevoflurane is often used in pediatric anesthesia and is associated with high incidence of psychomotor agitation. In such cases, dexmedetomidine (DEX) has been used, but its benefit and implications remain uncertain. We assessed the effects of DEX on agitation in children undergoing general anesthesia with sevoflurane. Method: Meta-analysis of randomized clinical and double-blind studies, with children undergoing elective procedures under general anesthesia with sevoflurane, using DEX or placebo. We sought articles in English in PubMed database using the following terms: Dexmedetomidine, sevoflurane (Methyl Ethers/sevoflurante), and agitation (Psychomotor Agitation). Duplicate articles with children who received premedication and used active control were excluded. It was adopted random effects model with DerSimonian–Laird testing and odds ratio (OR) calculation for dichotomous variables, and standardized mean difference for continuous variables, with their respective 95% confidence interval (CI). Results: Of 146 studies identified, 10 were selected totaling 558 patients (282 in DEX group and 276 controls). The use of DEX was considered a protective factor for psychomotor agitation (OR = 0.17; 95% CI 0.13–0.23; p < 0.0001) and nausea and vomiting in PACU (OR = 0.49; 95% CI 0.35–0.68; p < 0.0001). Wake-up time and PACU discharge time were higher in the dexmedetomidine group. There was no difference between groups for extubation time and duration of anesthesia. Conclusion: Dexmedetomidine reduces psychomotor agitation during wake-up time of children undergoing general anesthesia with sevoflurane. Resumo: Justificativa e objetivos: Sevoflurano é frequentemente usado em anestesia pediátrica e está associado à alta incidência de agitação psicomotora ao despertar. Nesses casos a dexmedetomidina (dex) tem sido usada, porém permanecem incertos seus benefícios e suas implicações. Foram avaliados os efeitos da dex sobre a agitação no despertar de crianças submetidas à anestesia geral com sevoflurano. Método: Metanálise de ensaios clínicos randomizados e duplamente encobertos, com crianças submetidas a procedimentos eletivos sob anestesia geral com sevoflurano, que usaram dex ou placebo. Buscaram-se artigos em língua inglesa na base de dados Pubmed com termos como Dexmedetomidine, sevoflurane (Methyl Ethers/sevoflurane) e agitation (Psychomotor Agitation). Artigos duplicados, com crianças que receberam medicação pré-anestésica e que usaram controle ativo foram excluídos. Adotou-se modelo de efeitos aleatórios com testes de DerSimonian-Laird e cálculo de odds ratio (OR) para variáveis dicotômicas e diferença de média padronizada para variáveis contínuas, com seus respectivos intervalos de confiança de 95% (IC). Resultados: Dos 146 estudos identificados, 10 foram selecionados, com 558 pacientes (282 no grupo dex e 276 controles). O uso da dex foi considerado fator de proteção para agitação psicomotora (OR = 0,17; 95% IC 0,13-0,23; p < 0,0001) e para náuseas e vômitos na SRPA (OR = 0,49; 95% IC 0,35-0,68; p < 0,0001). Tempo para despertar e para alta da SRPA foram maiores no grupo dexmedetomidina. Não houve diferença entre os grupos para tempo de extubação e duração da anestesia. Conclusão: A dexmedetomidina reduz a agitação psicomotora no despertar de crianças submetidas à anestesia geral com sevoflurano. Keywords: General anesthesia, Inhalational anesthetics, Dexmedetomidine, Psychomotor agitation, Meta-analysis, Palavras-chave: Anestesia geral, Anestésicos inalatórios, Dexmedetomidina, Agitação psicomotora, Metanálise